Numerical Study Characteristics of Heat Transfer on Staggered Cylinder Arrangement - Sulharman, Sulharman; Setiawan, M. Yasep (IPTEK The Journal for Technology and Science, 2012)
This research was conducted to examine the characteristics of heat transfer and heat flux fluctuations of staggered cylinder arrangement. The parameters in this study is Reynolds 8.8x104 , inlet velocity of 1 m/s and inlet temperature of 600C. Numerical model used is a 2D model-URANS turbulence model is k-omega SST. The results of this study indicate that increased flow velocity in the narrow area on the second row and third row caused by the staggered arrangement. This led to the distribution of the local Nusselt third highest row two and row after row of the lowest. Highest temperature distribution found in the area and the intensity of the turbulent wake in the third row higher value this is due to the influence of turbulence on the previous line and the arrangement of the cylinders. Effect of heat flux variation of the average Nusselt number appears lower in the heat flux 600 W/m2 than 200 W/m2 and 1000 W/m2 , but the third row average Nusselt values coincide with each other. While the average turbulent intensity increases towards the downstream. In the third row with a heat flux of 600 W/m2 has the highest turbulence intensity, while for the heat flux and heat flux of 200 W/m2 1000 W/m2 intensity turbulennya coincide with each other.